MIKROTIK SOHO (Small Office Home Office) NETWORK WORKSHOP - wawan nurmansyah; Achmad Alfian; Meylinda Mulyati; Klaudius Jevanda (Yogyakarta State University, 2021)
Schools are generally used as places for formal community education, schools continue to evolve in terms of infrastructure development, human resources, especially teachers, and a curriculum system to keep up with the evolving times. Vocational High School prepares students who are ready to work, especially industries that need human resources who already have the required hard skills.Especially for the TKJ (computer network) concentration, students are given a workshop from the continuation of the socialization that had been previously held. The workshops are conducted online using video conferencing with the google meet application, applications such as power points and other application simulators are displayed by sharing the desktop view with workshop participants (students of SMK Xaverius 1 Palembang)Indicators for the assessment of workshop activities using a questionnaire and the results of several question points responded to by 22 students of SMK Xaverius Palembang. The highest percentage of questions